Indikasi Tindakan Sectio Caesarea di RSUD Sanjiwani Gianyar Tahun 2017-2019 - Ida Bagus Giri Sena Putra; I Made Wandia; Saktivi Harkitasari (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2021)
Abstrak Sectio Caesarea (SC) merupakan tindakan pembedahan untuk melahirkan janin dengan cara membuat sayatan untuk membuka dinding perut dan dinding uterus atau suatu histerotomi untuk mengeluarkan janin yang berada di dalam rahim ibu. Angka persalinan SC di Indonesia terus mengalami peningkatan pada tahun 2018. Persalinan dengan metode SC menunjukan angka 17,6 % dari seluruh jumlah persalinan di Indonesia, angka ini melebihi standar WHO yaitu 15 %. Menurut data tahun 2018, Bali menempati posisi kedua terbesar di Indonesia untuk persalinan melalui metode SC dengan persentase 30.2%. Jumlah ini meningkat hampir dua kali lipat dibandingkan data 2013 sebanyak 17.3%. Tujuan dari penelitian ini untuk mengetahui proporsi indikasi tindakan SC di RSUD Sanjiwani Gianyar Tahun 2017-2019. Proporsi ini mencakup gambaran responden yang melakukan tindakan SC berdasarkan indikasi SC, usia, pendidikan, dan pekerjaan. Penelitian ini menggunakan desain deskriptif dengan pendekatan cross-sectional. Hasil penelitian ini didapatkan usia responden terbanyak pada rentang usia 30-34 tahun sebanyak 65 (26,0%) orang, pendidikan responden bersalin dengan metode SC terbanyak adalah SMA sebanyak 123 (49,2) orang, pekerjaan terbanyak responden bersalin dengan metode SC adalah tidak bekerja sebanyak 124 (49,6%) orang, dan proporsi tertinggi indikasi SC yaitu persalinan SC berulang sebanyak 79 (31,6%) orang. Saran diharapkan untuk penelitian selanjutnya agar dapat memuat lebih banyak indikasi SC khususnya yang dilakukan di RSUD Sanjiwani Gianyar. Kata kunci: Sectio Caesarea, Indikasi, RSUD Sanjiwani,Bali Abstract [Indications for Sectio Caesarea at the Sanjiwani Hospital, Gianyar in 2017-2019] Sectio Caesarea (SC) is a surgical procedure to give birth to a fetus by making an incision to open the abdominal wall and uterine wall or a hysterotomy to remove the fetus in the mother's womb. The SC delivery rate in Indonesia continues to increase in 2018, with the SC method showing the rate of SC in 2018 was 17.6% of the total number of deliveries in Indonesia, this figure exceeds the WHO standard of 15%. The data from 2018 showed that Bali occupies the second largest position in Indonesia with deliveries through the SC method with a percentage of 30.2%, this number has almost doubled compared to data from 2013, which was 17.3%. The purpose of this study was to determine the proportion of indications for SC at Sanjiwani Hospital, Gianyar in 2017-2019. This proportion includes the description of respondents who perform SC based on SC indications, age, education level, and occupation. This study was a descriptive design with a cross-sectional approach. This research sample must meet the inclusion criteria of maternity women using the SC method recorded in the medical records at Sanjiwani Hospital in 2019 and the exclusion criteria of incomplete medical records data. The results of this study found that the most respondent were in the age range of 30-34 years old as many as 65 (26.0%) people, the level education of respondents who gave birth using the SC method was high school graduates as many as 123 (49.2%) people, the occupation of most of the respondents who gave birth with the SC method were unemployed as many as 124 (49.6%) people, and the highest proportion of CS indications, namely repeated CS deliveries as many as 79 (31.6%) people. Suggestions are expected for further research so that it can contain more SC indications, especially those carried out at the Sanjiwani Hospital, Gianyar. Keywords: Sectio Caesarean, Indication, Sanjiwani Hospital, Bali